Thrombomodulin-independent activation of protein C and specificity of hemostatically active snake venom serine proteinases - Crystal structures of native and inhibited Agkistrodon contortrix contortrix protein C activator - Murakami, M. T.; Arni, R. K. (Amer Soc Biochemistry Molecular Biology Inc, 2005)
Protein C activation initiated by the thrombin-thrombomodulin complex forms the major physiological anticoagulant pathway. Agkistrodon contortrix contortrix protein C activator, a glycosylated single-chain serine proteinase, activates protein C without relying on thrombomodulin. The crystal structures of native and inhibited Agkistrodon contortrix contortrix protein C activator determined at 1.65 and 1.54 angstrom resolutions, respectively, indicate the pivotal roles played by the positively charged belt and the strategic positioning of the three carbohydrate moieties surrounding the catalytic site in protein C recognition, binding, and activation. Structural changes in the benzamidine-inhibited enzyme suggest a probable function in allosteric regulation for the anion-binding site located in the C-terminal extension, which is fully conserved in snake venom serine proteinases, that preferentially binds Cl1- instead of SO42-.